2018
DOI: 10.21859/jech.5.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Health Literacy and Addiction among Women of Reproductive Age Referring to Addiction Treatment Centers in Tehran, Iran

Abstract: Background and Objective: Health literacy can affect individuals' physical and psychological status and quality of life. Regarding this, the present study was conducted to determine the relationship between health literacy and addiction in women of reproductive age referring to addiction treatment centers in Tehran, Iran. Materials and Methods: This cross-sectional study was conducted on 141 women of reproductive age referring to the addiction treatment centers of Tehran in 2017. The study population was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Deegan and colleagues in 2019 showed that low to moderate levels of health literacy were common among those in substance abuse treatment [46]. Also, the results of Karimi et al 's research in 2017 indicated that women with higher health literacy have a lower tendency to addiction [47].…”
Section: Discussionmentioning
confidence: 99%
“…Deegan and colleagues in 2019 showed that low to moderate levels of health literacy were common among those in substance abuse treatment [46]. Also, the results of Karimi et al 's research in 2017 indicated that women with higher health literacy have a lower tendency to addiction [47].…”
Section: Discussionmentioning
confidence: 99%